The abscisic acid-related SNARE homolog NtSyr1 contributes to secretion and growth: evidence from competition with its cytosolic domain. - Geelen, D; Leyman, B; Batoko, H; Di Sansebastiano, G; Moore, I; Blatt, MR; Di Sansabastiano, G (2002)
Syntaxins and other SNARE proteins are crucial for intracellular vesicle trafficking, fusion, and secretion. Previously, we isolated the syntaxin-related protein NtSyr1 (NtSyp121) from tobacco in a screen for abscisic acid-related signaling elements, demonstrating its role in determining the abscisic acid sensitivity of K(+) and Cl(-) channels in stomatal guard cells. NtSyr1 is localized to the plasma membrane and is expressed normally throughout the plant, especially in root tissues, suggesting that it might contribute to cellular homeostasis as well as to signaling. To explore its functions in vivo further, we examined stably transformed lines of tobacco that expressed various constructs of NtSyr1, including the full-length protein and a truncated fragment, Sp2, corresponding to the cytosolic domain shown previously to be active in suppressing ion channel response to abscisic acid. Constitutively overexpressing NtSyr1 yielded uniformly high levels of protein (>10 times the wild-type levels) and was associated with a significant enhancement of root growth in seedlings but not with any obvious phenotype in mature, well-watered plants. Similar transformations with constructs encoding the Sp2 fragment of NtSyr1 showed altered leaf morphology but gave only low levels of Sp2 fragment, suggesting a strong selective pressure against plants expressing this protein. High expression of the Sp2 fragment was achieved in stable transformants under the control of a dexamethasone-inducible promoter. Sp2 expression was correlated positively with altered cellular and tissue morphology in leaves and roots and with a cessation of growth in seedlings. Overexpression of the full-length NtSyr1 protein rescued the wild-type phenotype, even in plants expressing high levels of the Sp2 fragment, supporting the idea that the Sp2 fragment interfered specifically with NtSyr1 function by competing with NtSyr1 for its binding partners. To explore NtSyr1 function in secretion, we used a green fluorescent protein (GFP)-based section assay. When a secreted GFP marker was coexpressed with Sp2 in tobacco leaves, GFP fluorescence was retained in cytosolic reticulate and punctate structures. In contrast, in plants coexpressing secreted GFP and NtSyr1 or secreted GFP alone, no GFP fluorescence accumulated within the cells. A new yellow fluorescent protein-based secretion marker was used to show that the punctate structures labeled in the presence of Sp2 colocalized with a Golgi marker. These structures were not labeled in the presence of a dominant Rab1 mutant that inhibited transport from the endoplasmic reticulum to the Golgi. We propose that NtSyr1 functions as an element in SNARE-mediated vesicle trafficking to the plasma membrane and is required for cellular growth and homeostasis.